Assumindo novas identidades: resistência indígena no litoral sul do Espírito Santo (século XVIII) - Bourguignon, Leonardo Nascimento (2018)
During the first half of the 16th Century, indigenous resistance in the Captaincy of Espírito Santo, forced the Portuguese Crown to adopt a new colonizing policy, symbolized by the sending of Jesuits to America. In this context, were there created in the south of Espírito Santo, the missions of Guaraparim and Iriritiba, the current city of Anchieta. In this last one, the gravity and amplitude of a series of uprisings initiated in the year 1742 left startling civil and religious authorities. Inspired by the actions developed at these events and at other times by the different indigenous ethnic groups in that locality and those who lived in their surroundings, we defend the hypothesis that to survive all the transformations represented by colonization, those individuals reinvented themselves repeatedly, creating and assuming different identities in order to assure their interests. We also try to demonstrate, by reading the depositions of Indians and settlers rendered to a judicial processes in 1761, organized by the Inquisition against the Jesuits, and in the clues printed in the sources produced by the colonial power, that in these spaces there was a process of mutual influence that, the Indians beyond, transformed Brazilians, Portuguese and other non-Indians who lived and constituted, in a process of ethnogenesis, new types of societies.